2018
DOI: 10.1177/0095327x18756284
|View full text |Cite
|
Sign up to set email alerts
|

Countering Boko Haram’s Violence: A Deterrence–Backlash Perspective

Abstract: This article examines efforts to counter Boko Haram’s campaign of terrorism in Northern Nigeria from a deterrence–backlash perspective. Drawing from previous research, the authors develop hypothetical expectations for deterrence and backlash effects when counterterrorism policies are conducted at governmental and community levels. Using parametric survival analysis, the authors conclude that government policies designed to curb Boko Haram attacks resulted in backlash. Conversely, community-based efforts result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Any perceptions of the incident are likely impacted from forces within and outside of a given terrorist organization (Ross and Gurr, 1989), and, from a deterrence perspective, this framing drives any subsequent influences on terrorism through rational evaluations of the risks and rewards of terrorism. Other authors have suggested empirical models (Jiao and Luo, 2018;Sandler and Siqueira, 2006), as well as structural (Daxecker and Hess, 2013) and situational characteristics to maximize possible deterrent outcomes across numerous states and conflicts (Dear, 2013;Dulin and Patiño, 2018;Gill et al, 2016). Given the complex decision-making processes of terrorist organizations (Victoroff, 2005), targeted killings may simultaneously both increase or decrease terrorism from different actors through processes not limited to deterrence.…”
Section: Divergent Responses To Targeted Killingsmentioning
confidence: 99%
“…Any perceptions of the incident are likely impacted from forces within and outside of a given terrorist organization (Ross and Gurr, 1989), and, from a deterrence perspective, this framing drives any subsequent influences on terrorism through rational evaluations of the risks and rewards of terrorism. Other authors have suggested empirical models (Jiao and Luo, 2018;Sandler and Siqueira, 2006), as well as structural (Daxecker and Hess, 2013) and situational characteristics to maximize possible deterrent outcomes across numerous states and conflicts (Dear, 2013;Dulin and Patiño, 2018;Gill et al, 2016). Given the complex decision-making processes of terrorist organizations (Victoroff, 2005), targeted killings may simultaneously both increase or decrease terrorism from different actors through processes not limited to deterrence.…”
Section: Divergent Responses To Targeted Killingsmentioning
confidence: 99%
“…28 Nigeria also adopted an unconventional CT approach by enlisting local volunteers into what became known as the Civilian Joint Task Force (CJTF) drawn from among the youths, hunters, vigilante groups, and farmers, whose activities, according to Dulin and Patino, had a deterrence effect on terrorist attacks in the northeast, owing to internal communal mechanism in the group's engagement. 29 For reasons of their good knowledge of the terrain and demographics, CJTF troops acted as the de-facto intelligence apparatus of the larger CT operations and in a particular instance foiled an attempted bombing in the Maiduguri Internally Displaced Persons camp in March 2014. 30 In a similar unconventional instance, Nigeria engaged the service of private defense forces from South Africa known as Specialized Tasks, Trainings, Equipment and Protection (STTEP), whose activities were reportedly instrumental to the early 2015 dislodgement of Boko Haram terrorists in the northeast.…”
Section: Nigeria's Domestic Counter-terrorism Programs and Strategies...mentioning
confidence: 99%
“…Several tactics, places and conflicts have been examined. Examples include, but are not limited to, military retaliatory bombings in Libya (Enders & Sandler, 1993), British anti‐terrorism strategies in Northern Ireland (LaFree et al., 2009), state interventions against the Euzkadi Ta Askatasuna (Argomaniz & Vidal‐Diez, 2015) and Boko Haram (Dulin & Patino, 2018), military counterinsurgency operations in Pakistan (Rehman et al., 2017), and Israeli repressive actions within the Israeli–Palestinian conflict (Carson, 2017; Dugan & Chenoweth, 2012b; Hafez & Hatfield, 2006; Sharvit et al., 2013). Nevin (2003), who found that violent governmental retaliation increased the severity of terrorist activities across different historical cases of terrorism and government repression, provides further corroboration of backlash effects.…”
Section: Research Backgroundmentioning
confidence: 99%